MiR-181b suppress glioblastoma multiforme growth through inhibition of SP1-mediated glucose metabolism - Yin, JianXing (Cancer Cell Int, 2020)
BACKGROUND: Glucose metabolic reprogramming is a significant hallmark of malignant tumors including GBM. Previous studies suggest that microRNAs play key roles in modulating this process in GBM cells. miR-181b acts as a tumor suppressor miRNA in influencing glioma tumorigenesis. Our previous results showed that miR-181b was down-regulated in glioma cells and tissues. METHODS: The extracellular acidification rate (ECAR), colony formation assay and levels of Glut1 and PKM2 were measured to assess the glucose metabolic and proliferation changes in GBM cells overexpressing miR-181b. Immunoblotting and luciferase reporter assay were performed to confirm the expression and role of SP1 as a direct target of miR-181b. ChIP assay was used to figure out the transcriptional regulation of SP1 on Glut1 and PKM2. In vivo study was examined for the role of miR-181b in GBM cells. RESULTS: MiR-181b overexpression significantly reduced the glucose metabolic and colony formation ability of GBM cells. And, SP1 was confirmed as a direct target of miR-181b while upregulation of SP1 could reverse the influence of overexpression of miR-181b. Furthermore, Glut1 and PKM2 could be regulated by SP1. Finally, miR-181b could inhibit the tumor growth in vivo. CONCLUSIONS: Our article demonstrated the inhibitory effect of miR-181b on glucose metabolism and proliferation in GBM by suppressing SP1 expression.